An Ausubelian approach to physics instruction : an experiment in an introductory college course in eletromagnetism - Moreira, Marco Antonio (1977)
Based on the learning theory of David Ausubel, an experimental introductory college physics course in electromagnetism was organized and taught to students of science and engineering. Four equivalent groups of students, forming two pairs of experimental-control groups participated in the study. One of these pairs was taught under a selfpaced format and the other under a traditional lecture approach. According to Ausubel's theory, the most inclusive, most general ideas, phenomena, and concepts should be presented early in instruction to serve as conceptual "anchorage" for subsequent learning. Following this principle, Maxwell's Equations and inclusive concepts such as electromagnetic force and electromagnetic field were introduced, in the experimental groups, at the beginning of the course in order to serve as basis for subsequent presentation of electric and magnetic phenomena. The control groups followed a traditional content organization found in most textbooks on the subject, which starts with electricity, followed by magnetism, and ends with electromagnetic phenomena and the Maxwell Equations. Traditional achievement measures and concept association tests were used to search for differences, that could arise from the two different organizational approaches, in terms of the student's ability to apply, relate, differentiate and hierarchically organize electromagnetic concepts. No significant differences in achievement were found in terms of traditional measures such as unit-tests, quizzes and exams. However, in terms of concept learning there was evidence that the Ausubelian approach fostered concept differentiation, relatedness and meaningful hierarchical organization to a greater extent than the traditional approach, specially in the self-paced program comparisons. These results are both consitent with and supportive of Ausubel's theory and provide evidence that lhis theory is useful for physics instruction and for research in physics education.